Depiction of microglial activation in aging and dementia: Positron emission tomography with [11C]DPA713 versus [11C](R)PK11195. Issue 3 (March 2017) - Yokokura, Masamichi; Terada, Tatsuhiro; Bunai, Tomoyasu; Nakaizumi, Kyoko; Takebayashi, Kiyokazu; Iwata, Yasuhide; Yoshikawa, Etsuji; Futatsubashi, Masami; Suzuki, Katsuaki; Mori, Norio; Ouchi, Yasuomi
The presence of activated microglia in the brains of healthy elderly people is a matter of debate. We aimed to clarify the degree of microglial activation in aging and dementia as revealed by different tracers by comparing the binding potential (BPND ) in various brain regions using a first-generation translocator protein (TSPO) tracer [ 11 C]( R )PK11195 and a second-generation tracer [ 11 C]DPA713. The BPND levels, estimated using simplified reference tissue models, were compared among healthy young and elderly individuals and patients with Alzheimer's disease (AD) and were correlated with clinical scores. An analysis of variance showed category-dependent elevation in levels of [ 11 C]DPA713 BPND in all brain regions and showed a significant increase in the AD group, whereas no significant changes among groups were found when [ 11 C]( R )PK11195 BPND was used. Cognito-mnemonic scores were significantly correlated with [ 11 C]DPA713 BPND levels in many brain regions, whereas [ 11 C]( R )PK11195 BPND failed to correlate with the scores. As mentioned elsewhere, the present results confirmed that the second-generation TSPO tracer [ 11 C]DPA713 has a greater sensitivity to TSPO in both aging and neuronal degeneration than [ 11 C]( R )PK11195. Positron emission tomography with [ 11 C]DPA713 is suitable for the delineation of in vivo microglial activation occurring globally over the cerebral cortex irrespective of aging and degeneration.